Inventori perilaku kerja inovatif guru indonesia: analisis rasch model - Rais Hidayat; Baharuddin Baharuddin; Donna Sampaleng; Yuyun Elizabeth Patras (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The purpose of this research was to find the items of the teacher's innovative work behavior instrument during the Covid 19 pandemic and recommend several things to improve it. The teacher's innovative work behavior instrument was developed through a study of concepts and theories of innovative work behavior until a draft instrument was obtained that met content validity, logical validity, examination by experts to obtain expert validity, and testing of 10 teachers. Instruments that have been corrected based on input from the teacher are then distributed via google-form. Determination of the number of samples in this study using purposive sampling. In this study, researchers chose teachers as respondents with a sample size of 1200. Data analysis used the Rasch model. The findings of this research are that the teacher's innovative work behavior instrument during the Covid 19 period, which consists of 11 indicators based on the Rasch model, has met the requirements for use in research. This study recommends 5 things to improve PKIG, namely: (i) making scientific papers, (ii) learning that exceeds the standard, (iii) mentoring other teachers, (iv) pioneering the use of ICT for learning, and (v) struggling to get new ideas/products accepted by others. Based on these recommendations, the implications of this research are that teachers need to be encouraged to conduct research in schools, teach exceeding standards, monitor each other among teachers, cultivate a culture of using learning technology, and promote all teacher innovation products to other parties.